2006
DOI: 10.1161/circulationaha.106.636977
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Heart Disease Events Triggered by Short-Term Exposure to Fine Particulate Air Pollution

Abstract: Background-Recent evidence suggests that long-term exposure to particulate air pollution contributes to pulmonary and systemic oxidative stress, inflammation, progression of atherosclerosis, and risk of ischemic heart disease and death. Short-term exposure may contribute to complications of atherosclerosis, such as plaque vulnerability, thrombosis, and acute ischemic events. These findings are inconclusive and controversial and require further study. This study evaluates the role of short-term particulate expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
295
7
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 534 publications
(329 citation statements)
references
References 46 publications
14
295
7
13
Order By: Relevance
“…Significant PM 2.5 effects were observed only for patients with existing CAD. These results are largely consistent with previously reported results16, 17 and suggest that elevated PM 2.5 exposures can contribute to triggering of acute coronary events, acutely destabilizing and rupturing atherosclerotic plaque, in those with existing clinically significant CAD but not in those with clean coronary arteries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Significant PM 2.5 effects were observed only for patients with existing CAD. These results are largely consistent with previously reported results16, 17 and suggest that elevated PM 2.5 exposures can contribute to triggering of acute coronary events, acutely destabilizing and rupturing atherosclerotic plaque, in those with existing clinically significant CAD but not in those with clean coronary arteries.…”
Section: Discussionsupporting
confidence: 92%
“…Odds ratios using both the standard linear and threshold models were estimated for all ACS, STEMI, NSTEMI, UA, and NSTE‐ACS events for all patients and for patients with and without CAD. For comparison purposes, and consistent with reporting from various studies and reviews of the literature,1, 2, 3, 4, 5, 6, 7, 8, 11, 14, 15, 16 odds ratios associated with 10‐μg/m 3 incremental increases in PM 2.5 concentration are presented.…”
Section: Methodsmentioning
confidence: 93%
“…Recent studies (21, 58) have shown that commonly encountered levels of airborne pollutants can result in a prohypertensive response in humans that may be exaggerated in predisposed individuals. This potentiating effect of inhaled particulates has been noted with other chronic conditions or risk factors such as atherosclerosis, diabetes, and postmenopausal status (31,40,49). Although the precise mechanisms remain elusive, there is increasing evidence that PM 2.5 exposure results in rapid changes in the vasculature (7, 32).…”
mentioning
confidence: 97%
“…The analysis from a population of 50 million living in the major U.S. cities (The National Morbidity, Mortality and Air Pollution Study) indicated that an increase of 10 μg/m 3 in PM 10 was related to an increase in 0.68% in cardiopulmonary mortality 23, 24, 25. Every 10 μg/m 3 increase in PM 2.5 exposure was also associated with an increase in 4.5% in coronary artery disease (CAD) 26. Conversely, it was estimated that each 10 μg/m 3 decrease in PM 2.5 was associated with an increase in 0.61 years in mean life expectancy in the United States 27.…”
Section: Pm and Cardiovascular Diseasesmentioning
confidence: 99%